Disclosure Determinants of Provincial Financial Statements - Hardiningsih, Pancawati; Pramudibyanto, Hascaryo; Kristiana, Ida; Suhadi, Suhadi (Universitas Muhammadiyah Magelang, 2022)
Disclosure and provision of information is an important element in financial statements. Therefore, local governments must provide adequate disclosure of various information in financial reports as a form of accountability and transparency of public finances to avoid errors and misunderstandings in the interpretation of financial statements. This study aims to analyze the factors that influence the level of disclosure of the Provincial Government's Financial Statements for the 2018-2020 fiscal year. The sample used in this study were 101 Financial Statements with the census method. This research analysis technique uses multiple linear regression analysis with Eviews 8.0 application. The results showed that regional wealth, government size, and the number of SKPDs had a positive effect on the level of LKPD disclosure. While the level of dependency and the number of audit findings does not affect the disclosure of LKPD.